A method of water-based tape casting to produce an alumina ceramic substrate
By using a specific ternary composite bonding/thickening system and process, the environmental and safety hazards of oil-based casting methods and the problems of long drying time and degreasing cracking in water-based casting methods have been solved, realizing the preparation of high-strength, low-cost alumina ceramic substrates and possessing environmentally friendly and high-performance water-based casting molding technology.
Patent Information
- Application Number
- CN202611348650.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-11-03
AI Technical Summary
Existing oil-based casting methods have environmental and safety hazards, unstable slurry and green body quality, frequent defects in the debinding and sintering processes, and high costs when preparing ceramic substrates. In addition, water-based casting methods have shortcomings such as long drying time, debinding cracking, and thickness limitations.
A specific ternary composite binder/thickener system, including micron-sized ceramic powder, deionized water, dispersant, binder, thickener, and plasticizer, is used to prepare a high-strength, low-carbon-residue alumina ceramic substrate through vacuum degassing and casting, combined with warm pressing and sintering processes.
It achieves VOC-free, water-based green production, with high green forming rate, good flexibility, high density of ceramic substrate, significantly improved bending strength, low thickness shrinkage, and higher thermal conductivity and dielectric constant, thus reducing production costs.
Smart Images

Figure CN123026435A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic non-metallic materials, specifically relating to a method for preparing alumina ceramic substrates by water-based casting molding. Background Technology
[0002] Ceramic substrates, as core supporting components for high-power semiconductor modules, 5G communication devices, and electronic components in new energy vehicles, require high insulation, high thermal conductivity, excellent mechanical properties, and precise dimensional accuracy. Casting is currently the mainstream process for the industrial mass production of thin and ultra-thin ceramic substrates (thickness 50 μm to 1.5 mm). Among these, oil-based casting has long held a dominant position due to the use of organic solvents as the dispersion medium. However, existing oil-based casting methods suffer from numerous drawbacks, including environmental and safety concerns, unstable slurry and green body quality, frequent defects during debinding and sintering processes, and high costs.
[0003] Water-based tape casting offers significant advantages such as environmental friendliness, safety, and low cost. For example, Chinese patent application CN119751083A discloses a method for preparing silicon nitride ceramic substrates using a tape casting process with polyvinyl alcohol (PVA) as a binder. However, this method suffers from drawbacks such as long drying time, easy cracking during degreasing, and thickness limitations. Therefore, developing a water-based tape casting process that does not require organic solvents, effectively shortens drying time, avoids degreasing cracking, and overcomes thickness limitations is a pressing challenge in this field. Summary of the Invention
[0004] To overcome the aforementioned technical problems, this invention provides a method for preparing alumina ceramic substrates using water-based casting molding. This method achieves VOC-free, fully water-based green production through a specific ternary composite binder / thickener system, while simultaneously imparting excellent rheological properties, high strength, and low residual carbon content to the green body.
[0005] The specific technical solution adopted by this invention is as follows: This invention provides a method for preparing alumina ceramic substrates using water-based casting molding, comprising the following processing steps: S1. Based on 100 parts by weight of micron-sized ceramic powder, the micron-sized ceramic powder, 60-70 parts by weight of deionized water, and 3-6 parts by weight of dispersant are ball-milled and mixed to prepare the first slurry. S2. Add 15-25 parts by weight of binder, 5-10 parts by weight of thickener and 5-8 parts by weight of plasticizer to the first slurry and ball mill to prepare the second slurry. S3. Add 1 to 2 parts of defoamer to the second slurry and mix evenly to prepare the third slurry; S4. The third slurry is placed in a vacuum degassing machine for vacuum degassing; S5. Place the degassed casting slurry into the casting machine for casting to obtain a green ceramic tape. After drying, cut it to obtain green ceramic pieces. S6. The green ceramic pieces are stacked and warm-pressed to form a blank, and the pressed blank is placed in a debinding furnace for debinding. S7. Place the debonded blank into a sintering furnace for calcination, and then cool it with the furnace to obtain a ceramic substrate.
[0006] Further, in step S1, the particle size of the micron-sized ceramic powder is 1-3 μm; based on a total mass of 100 parts by weight, it consists of 90-95 parts by weight of micron-sized alumina powder and 5-10 parts by weight of sintering aid; the sintering aid is one or more of magnesium-calcium-silicon glass, yttrium oxide, dysprosium oxide, and lithium carbonate.
[0007] Further, in step S1, the dispersant is one or more of ammonium citrate, polyacrylic acid, and tetramethylammonium hydroxide.
[0008] Further, in step S2, the adhesive is a mixture of polyvinyl alcohol and styrene-butadiene rubber; the thickener is one or both of hydrogen carboxymethyl cellulose and lithium carboxymethyl cellulose; and the plasticizer is one or more of glycerol, polyethylene glycol, and dibutyl phthalate.
[0009] Furthermore, based on 100 parts by weight of the micron-sized ceramic powder, the content of polyvinyl alcohol is 5-10 parts by weight, the content of styrene-butadiene rubber is 10-15 parts by weight, and the content of thickener is 5-10 parts by weight.
[0010] Further, in step S3, the defoamer is one or more of tributyl phosphate and silicone oil.
[0011] Furthermore, in step S4, the vacuum degassing pressure is 0.1–0.3 MPa and the time is 0.2–0.5 h.
[0012] Furthermore, in step S5, the height of the squeegee during casting is 1 mm, the casting substrate is a silicone resin coated PET film, and the specific drying process is as follows: first pre-drying in the range of 35 to 40 ℃ for 10 min, and finally drying in the range of 50 to 70 ℃ for 10 min.
[0013] Further, in step S6, the temperature of the warm-pressing process is 45-120 ℃, the pressure is 10-50 MPa, and the holding time is 1-2 h; the temperature of the glue discharge process is 200 ℃-600 ℃, and the holding time is 2-3 h.
[0014] Further, in step S7, the specific process of calcination is as follows: heating to 1500 ℃~1600 ℃ at a heating rate of 5 ℃ / min in an air atmosphere, and holding at that temperature for 2~4 h.
[0015] The technical effects achieved by this invention are as follows: 1. This invention uses styrene-butadiene rubber (SBR) and hydrogen / lithium type carboxymethyl cellulose to partially replace polyvinyl alcohol (PVA), forming a synergistic system that combines dispersion stability and high-efficiency bonding, significantly reducing slurry viscosity and increasing solid content.
[0016] 2. The green ceramic blanks prepared by the method provided by the present invention have high forming rate, good flexibility, and are not easy to crack. After sintering, the ceramic substrate has high density, significantly improved bending strength (up to 394 MPa), low thickness shrinkage, higher thermal conductivity, and greater dielectric constant.
[0017] 3. The carboxymethyl cellulose used in the method provided by the present invention has an auxiliary dispersing effect, which can significantly reduce or even completely replace the use of traditional dispersants and reduce production costs. Attached Figure Description
[0018] Figure 1 These are TG-DSC curves for Embodiment 1 and Comparative Example 2 of the present invention; Figure 2 These are SEM images of embodiments of the present invention, where a is Example 1, b is Example 2, c is Comparative Example 1, and d is Comparative Example 2. Figure 3 This is a comparison chart of the green body forming rates prepared in the embodiments and comparative examples of the present invention; Figure 4 This is a comparison chart of the thickness shrinkage rate of ceramic substrates prepared in the embodiments and comparative examples of the present invention; Figure 5 This is a comparison diagram of the bending strength of ceramic substrates prepared in the embodiments and comparative examples of the present invention; Figure 6 This is a comparison diagram of the thermal conductivity of ceramic substrates prepared in the embodiments and comparative examples of the present invention; Figure 7 This is a comparison diagram of the dielectric constants of the ceramic substrates prepared in the embodiments and comparative examples of the present invention. Detailed Implementation
[0019] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0020] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0021] Secondly, the term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in a preferred embodiment" appearing in different places throughout this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that mutually excludes other embodiments.
[0022] Furthermore, the present invention will be described in detail with reference to the schematic diagrams. When describing the embodiments of the present invention in detail, the schematic diagrams are merely examples for ease of explanation and should not limit the scope of protection of the present invention.
[0023] Example 1 A method for preparing alumina ceramic substrates using water-based casting molding, the method being as follows: S1. Weigh 100 parts by weight of ceramic powder according to the relative proportion based on the mass of ceramic powder, wherein the ceramic powder contains 95 parts by weight of 1.5μm alumina powder, 5 parts by weight of magnesium-calcium-silicon glass sintering aid, 65 parts by weight of deionized water, and 4 parts by weight of ammonium citrate dispersant. After ball milling and mixing, the first slurry is prepared.
[0024] S2. Weigh 8 parts by weight of polyvinyl alcohol adhesive, 13 parts by weight of styrene-butadiene rubber adhesive, 8 parts by weight of hydrogen carboxymethyl cellulose thickener, and 7 parts by weight of glycerol water-based plasticizer according to the relative proportions based on the mass of ceramic powder. Add them to the first slurry and ball mill to prepare the second slurry.
[0025] S3. Add 2 parts by weight of defoamer to the second slurry prepared in S2 to prepare the third slurry.
[0026] S4. Place the slurry from S3 into a vacuum degassing machine for vacuum degassing. The vacuum degassing machine pressure is 0.2 MPa, and the time is 0.5 h.
[0027] S5. Place the degassed casting slurry into the casting machine with the doctor blade height at 1 mm, and cast the slurry onto a silicone-coated PET film to prepare a cast sheet. Then transfer it to a dryer for low-temperature drying, first pre-drying at 35 ℃ for 10 min, and finally drying at 60 ℃ for 10 min. After drying, cut to obtain green ceramic sheets.
[0028] S6. The green ceramic sheets are stacked in a certain number of layers, and the ceramic green body is warm-pressed at 80 ℃ with a pressure of 30 MPa for 2 hours. The binder of the ceramic green body obtained by warm pressing is removed by holding it at 600 ℃ for 3 hours.
[0029] S7. Place the debinding blank into a sintering furnace and calcine it. Under an air atmosphere, heat it to 1600 ℃ at a heating rate of 5 ℃ per minute, hold it at that temperature for 3 h, and then cool it with the furnace to obtain a ceramic substrate.
[0030] Example 2 A method for preparing alumina ceramic substrates using water-based casting molding, the method being as follows: S1. Weigh 100 parts by weight of ceramic powder according to the relative proportion based on the mass of ceramic powder, wherein the ceramic powder contains 95 parts by weight of 1.5μm alumina powder, 5 parts by weight of magnesium-calcium-silicon glass sintering aid, 65 parts by weight of deionized water, and 4 parts by weight of ammonium citrate dispersant. After ball milling and mixing, the first slurry is prepared.
[0031] S2. Weigh 5 parts by weight of polyvinyl alcohol adhesive, 13 parts by weight of styrene-butadiene rubber adhesive, 10 parts by weight of hydrogen carboxymethyl cellulose thickener, and 7 parts by weight of glycerol water-based plasticizer according to the relative proportions based on the mass of ceramic powder. Add them to the first slurry and ball mill to prepare the second slurry.
[0032] S3. Add 2 parts by weight of defoamer to the second slurry prepared in S2 to prepare the third slurry.
[0033] S4. Place the slurry from S3 into a vacuum degassing machine for vacuum degassing. The vacuum degassing machine pressure is 0.2 MPa, and the time is 0.5 h.
[0034] S5. Place the degassed casting slurry into the casting machine with the doctor blade height at 1 mm, and cast the slurry onto a silicone-coated PET film to prepare a cast sheet. Then transfer it to a dryer for low-temperature drying, first pre-drying at 35 ℃ for 10 min, and finally drying at 60 ℃ for 10 min. After drying, cut to obtain green ceramic sheets.
[0035] S6. The green ceramic sheets are stacked in a certain number of layers, and the ceramic green body is warm-pressed at 80 ℃ with a pressure of 30 MPa for 2 hours. The binder of the ceramic green body obtained by warm pressing is removed by holding it at 600 ℃ for 3 hours.
[0036] S7. Place the debinding blank into a sintering furnace and calcine it. Under an air atmosphere, heat it to 1600 ℃ at a heating rate of 5 ℃ per minute, hold it at that temperature for 3 h, and then cool it with the furnace to obtain a ceramic substrate.
[0037] Example 3 A method for preparing alumina ceramic substrates using water-based casting molding, the method being as follows: S1. Weigh 100 parts by weight of ceramic powder according to the relative proportion based on the mass of ceramic powder, wherein the ceramic powder contains 95 parts by weight of 1.5μm alumina powder, 5 parts by weight of magnesium-calcium-silicon glass sintering aid, 65 parts by weight of deionized water, and 4 parts by weight of ammonium citrate dispersant. After ball milling and mixing, the first slurry is prepared.
[0038] S2. Weigh 6 parts by weight of polyvinyl alcohol adhesive, 12 parts by weight of styrene-butadiene rubber adhesive, 6 parts by weight of hydrogen carboxymethyl cellulose thickener, and 7 parts by weight of glycerol water-based plasticizer according to the relative proportions based on the mass of ceramic powder. Add them to the first slurry and ball mill to prepare the second slurry.
[0039] S3. Add 2 parts by weight of defoamer to the second slurry prepared in S2 to prepare the third slurry.
[0040] S4. Place the slurry from S3 into a vacuum degassing machine for vacuum degassing. The vacuum degassing machine pressure is 0.2 MPa, and the time is 0.5 h.
[0041] S5. Place the degassed casting slurry into the casting machine with the doctor blade height at 1 mm, and cast the slurry onto a silicone-coated PET film to prepare a cast sheet. Then transfer it to a dryer for low-temperature drying, first pre-drying at 35 ℃ for 10 min, and finally drying at 60 ℃ for 10 min. After drying, cut to obtain green ceramic sheets.
[0042] S6. The green ceramic sheets are stacked in a certain number of layers, and the ceramic green body is warm-pressed at 80 ℃ with a pressure of 30 MPa for 2 hours. The binder of the ceramic green body obtained by warm pressing is removed by holding it at 600 ℃ for 3 hours.
[0043] S7. Place the debinding blank into a sintering furnace and calcine it. Under an air atmosphere, heat it to 1600 ℃ at a heating rate of 5 ℃ per minute, hold it at that temperature for 3 h, and then cool it with the furnace to obtain a ceramic substrate.
[0044] Example 4 A method for preparing alumina ceramic substrates using water-based casting molding, the method being as follows: S1. Weigh 100 parts by weight of ceramic powder according to the relative proportion based on the mass of ceramic powder, wherein the ceramic powder contains 95 parts by weight of 1.5μm alumina powder, 5 parts by weight of magnesium-calcium-silicon glass sintering aid, 65 parts by weight of deionized water, and 4 parts by weight of ammonium citrate dispersant. After ball milling and mixing, the first slurry is prepared.
[0045] S2. Weigh 8 parts by weight of polyvinyl alcohol adhesive, 15 parts by weight of styrene-butadiene rubber adhesive, 5 parts by weight of hydrogen carboxymethyl cellulose thickener, and 7 parts by weight of glycerol water-based plasticizer according to the relative proportions based on the mass of ceramic powder. Add them to the first slurry and ball mill to prepare the second slurry.
[0046] S3. Add 2 parts by weight of defoamer to the second slurry prepared in S2 to prepare the third slurry.
[0047] S4. Place the slurry from S3 into a vacuum degassing machine for vacuum degassing. The vacuum degassing machine pressure is 0.2 MPa, and the time is 0.5 h.
[0048] S5. Place the degassed casting slurry into the casting machine with the doctor blade height at 1 mm, and cast the slurry onto a silicone-coated PET film to prepare a cast sheet. Then transfer it to a dryer for low-temperature drying, first pre-drying at 35 ℃ for 10 min, and finally drying at 60 ℃ for 10 min. After drying, cut to obtain green ceramic sheets.
[0049] S6. The green ceramic sheets are stacked in a certain number of layers, and the ceramic green body is warm-pressed at 80 ℃ with a pressure of 30 MPa for 2 hours. The binder of the ceramic green body obtained by warm pressing is removed by holding it at 600 ℃ for 3 hours.
[0050] S7. Place the debinding blank into a sintering furnace and calcine it. Under an air atmosphere, heat it to 1600 ℃ at a heating rate of 5 ℃ per minute, hold it at that temperature for 3 h, and then cool it with the furnace to obtain a ceramic substrate.
[0051] Example 5 A method for preparing alumina ceramic substrates using water-based casting molding, the method being as follows: S1. Weigh 100 parts by weight of ceramic powder according to the relative proportion based on the mass of ceramic powder, wherein the ceramic powder contains 95 parts by weight of 1.5μm alumina powder, 5 parts by weight of magnesium-calcium-silicon glass sintering aid, 65 parts by weight of deionized water, and 4 parts by weight of ammonium citrate dispersant. After ball milling and mixing, the first slurry is prepared.
[0052] S2. Weigh 5 parts by weight of polyvinyl alcohol adhesive, 15 parts by weight of styrene-butadiene rubber adhesive, 6 parts by weight of hydrogen carboxymethyl cellulose thickener, and 7 parts by weight of glycerol water-based plasticizer according to the relative proportions based on the mass of ceramic powder. Add them to the first slurry and ball mill to prepare the second slurry.
[0053] S3. Add 2 parts by weight of defoamer to the second slurry prepared in S2 to prepare the third slurry.
[0054] S4. Place the slurry from S3 into a vacuum degassing machine for vacuum degassing. The vacuum degassing machine pressure is 0.2 MPa, and the time is 0.5 h.
[0055] S5. Place the degassed casting slurry into the casting machine with the doctor blade height at 1 mm, and cast the slurry onto a silicone-coated PET film to prepare a cast sheet. Then transfer it to a dryer for low-temperature drying, first pre-drying at 35 ℃ for 10 min, and finally drying at 60 ℃ for 10 min. After drying, cut to obtain green ceramic sheets.
[0056] S6. The green ceramic sheets are stacked in a certain number of layers, and the ceramic green body is warm-pressed at 80 ℃ with a pressure of 30 MPa for 2 hours. The binder of the ceramic green body obtained by warm pressing is removed by holding it at 600 ℃ for 3 hours.
[0057] S7. Place the debinding blank into a sintering furnace and calcine it. Under an air atmosphere, heat it to 1600 ℃ at a heating rate of 5 ℃ per minute, hold it at that temperature for 3 h, and then cool it with the furnace to obtain a ceramic substrate.
[0058] Example 6 A method for preparing alumina ceramic substrates using water-based casting molding, the method being as follows: S1. Weigh 100 parts by weight of ceramic powder according to the relative proportion based on the mass of ceramic powder as the base material. The ceramic powder contains 95 parts by weight of 1.5 μm alumina powder and 5 parts by weight of magnesium-calcium-silicon glass sintering aid. After ball milling and mixing with 65 parts by weight of deionized water, the first slurry is prepared.
[0059] S2. Weigh 8 parts by weight of polyvinyl alcohol adhesive, 12 parts by weight of styrene-butadiene rubber adhesive, 8 parts by weight of hydrogen carboxymethyl cellulose thickener, and 7 parts by weight of glycerol water-based plasticizer according to the relative proportions based on the mass of ceramic powder. Add them to the first slurry and ball mill to prepare the second slurry.
[0060] S3. Add 2 parts by weight of defoamer to the second slurry prepared in S2 to prepare the third slurry.
[0061] S4. Place the slurry from S3 into a vacuum degassing machine for vacuum degassing. The vacuum degassing machine pressure is 0.2 MPa, and the time is 0.5 h.
[0062] S5. Place the degassed casting slurry into the casting machine with the doctor blade height at 1 mm, and cast the slurry onto a silicone-coated PET film to prepare a cast sheet. Then transfer it to a dryer for low-temperature drying, first pre-drying at 35 ℃ for 10 min, and finally drying at 60 ℃ for 10 min. After drying, cut to obtain green ceramic sheets.
[0063] S6. The green ceramic sheets are stacked in a certain number of layers, and the ceramic green body is warm-pressed at 80 ℃ with a pressure of 30 MPa for 2 hours. The binder of the ceramic green body obtained by warm pressing is removed by holding it at 600 ℃ for 3 hours.
[0064] S7. Place the debinding blank into a sintering furnace and calcine it. Under an air atmosphere, heat it to 1600 ℃ at a heating rate of 5 ℃ per minute, hold it at that temperature for 3 h, and then cool it with the furnace to obtain a ceramic substrate.
[0065] Comparative Example 1 A method for preparing alumina ceramic substrates using water-based casting molding, the method being as follows: S1. Weigh 100 parts by weight of ceramic powder according to the relative proportion based on the mass of ceramic powder as the base material. The ceramic powder contains 95 parts by weight of 1.5 μm alumina powder, 5 parts by weight of magnesium calcium silicate glass sintering aid, 65 parts by weight of deionized water, and 4 parts by weight of ammonium citrate dispersant. After ball milling and mixing, the first slurry is prepared.
[0066] S2. Weigh 15 parts by weight of styrene-butadiene rubber adhesive, 8 parts by weight of hydrogen carboxymethyl cellulose thickener, and 7 parts by weight of glycerol water-based plasticizer according to the relative proportions based on the mass of ceramic powder, add them to the first slurry, and ball mill to prepare the second slurry.
[0067] S3. Add 2 parts by weight of defoamer to the second slurry prepared in S2 to prepare the third slurry.
[0068] S4. Place the slurry from S3 into a vacuum degassing machine for vacuum degassing. The vacuum degassing machine pressure is 0.2 MPa, and the time is 0.5 h.
[0069] S5. Place the degassed casting slurry into the casting machine with the doctor blade height at 1 mm, and cast the slurry onto a silicone-coated PET film to prepare a cast sheet. Then transfer it to a dryer for low-temperature drying, first pre-drying at 35 ℃ for 10 min, and finally drying at 60 ℃ for 10 min. After drying, cut to obtain green ceramic sheets.
[0070] S6. The green ceramic sheets are stacked in a certain number of layers, and the ceramic green body is warm-pressed at 80 ℃ with a pressure of 30 MPa for 2 hours. The binder of the ceramic green body obtained by warm pressing is removed by holding it at 600 ℃ for 3 hours.
[0071] S7. Place the debinding blank into a sintering furnace and calcine it. Under an air atmosphere, heat it to 1600 ℃ at a heating rate of 5 ℃ per minute, hold it at that temperature for 3 h, and then cool it with the furnace to obtain a ceramic substrate.
[0072] Comparative Example 2 A method for preparing alumina ceramic substrates using water-based casting molding, the method being as follows: S1. Weigh 100 parts by weight of ceramic powder according to the relative proportion based on the mass of ceramic powder as the base material. The ceramic powder contains 95 parts by weight of 1.5 μm alumina powder, 5 parts by weight of magnesium calcium silicate glass sintering aid, 65 parts by weight of deionized water, and 4 parts by weight of ammonium citrate dispersant. After ball milling and mixing, the first slurry is prepared.
[0073] S2. Weigh 10 parts by weight of polyvinyl alcohol adhesive and 5 parts by weight of glycerol water-based plasticizer according to the relative proportion of ceramic powder as the base material, add them to the first slurry and ball mill to prepare the second slurry.
[0074] S3. Add 2 parts by weight of defoamer to the second slurry prepared in S2 to prepare the third slurry.
[0075] S4. Place the slurry from S3 into a vacuum degassing machine for vacuum degassing. The vacuum degassing machine pressure is 0.2 MPa, and the time is 0.5 h.
[0076] S5. Place the degassed casting slurry into the casting machine with the doctor blade height at 1 mm, and cast the slurry onto a silicone-coated PET film to prepare a cast sheet. Then transfer it to a dryer for low-temperature drying, first pre-drying at 35 ℃ for 10 min, and finally drying at 60 ℃ for 10 min. After drying, cut to obtain green ceramic sheets.
[0077] S6. The green ceramic sheets are stacked in a certain number of layers, and the ceramic green body is warm-pressed at 80 ℃ with a pressure of 30 MPa for 2 hours. The binder of the ceramic green body obtained by warm pressing is removed by holding it at 600 ℃ for 3 hours.
[0078] S7. Place the debinding blank into a sintering furnace and calcine it. Under an air atmosphere, heat it to 1600 ℃ at a heating rate of 5 ℃ per minute, hold it at that temperature for 3 h, and then cool it with the furnace to obtain a ceramic substrate.
[0079] like Figure 1 As shown, in Example 1, the decomposition temperatures of the three components are staggered (CMC→PVA→SBR), and the exothermic reaction is spread out into four broad small peaks; in Comparative Example 2, single PVA undergoes concentrated chain scission, forming a sharp large peak at 340℃. The peak height ratio is approximately 3:1, which means that the gas production rate per unit time differs by a factor of 3—this is precisely the root cause of "vigorous gas production causing bubbling defects."
[0080] Both curves support the 600℃ / 3h debinding regime for S6, but Comparative Example 2 did not complete decomposition at 600℃ (residual carbon oxidation dragged to above 620℃), and actually requires a higher debinding temperature or a longer holding time; Example 1 had already lost weight completely at 510℃, and there was sufficient margin for debinding at 600℃, which is also the process window advantage of the ternary system.
[0081] like Figure 2 As shown in the SEM images, the grains in Example 1 are uniformly grown and there are no obvious pores or bubbling defects inside; while Comparative Example 2 has a lot of micron-sized pores inside (caused by the ablation of residual carbon particles and the violent gas generation during degreasing).
[0082] The ceramic substrates prepared in Examples 1-6 and Comparative Examples 1-2 were compared, and the results are shown in the table below. Corresponding plots are drawn. Figures 3-7 : It is understood that the present invention uses a combination of styrene-butadiene rubber and hydrogen carboxymethyl cellulose to achieve the highest greening rate, the lowest shrinkage rate and the greatest mechanical strength of the ceramic substrate, which are far superior to those of commercial ceramic substrates.
[0083] This invention utilizes a styrene-butadiene rubber (SBR) and hydrogen-form carboxymethyl cellulose (HCMC) mixed binder to partially replace polyvinyl alcohol (PVA) in the preparation of ceramic substrates using water-based casting molding. This creates a synergistic system that combines dispersion stability with efficient bonding, achieving lower viscosity and higher solids content. It also improves slurry stability and leveling, shortens drying time, and increases molding efficiency. The resulting ceramic green bodies exhibit higher molding rates, better flexibility, and are less prone to cracking and powdering. They are easier to cut, punch, and laminate, with significantly improved dimensional uniformity and precision. During the debinding and sintering stage, this composite binder has a lower thermal decomposition temperature and more thorough debinding, resulting in a much lower residual carbon content than traditional PVA systems. This effectively avoids defects such as porosity and blistering, leading to higher density, more uniform microstructure, and superior dielectric, thermal conductivity, and mechanical properties in the ceramic substrate.
[0084] Meanwhile, this system is a fully water-based green system with no VOC emissions, low plasticizer usage, lower raw material costs and energy consumption, higher yield, and good compatibility with existing casting equipment. It is suitable for the preparation of various ceramic substrates such as alumina and aluminum nitride, and has outstanding advantages in improving the overall performance of substrates, simplifying processes, reducing costs, and ensuring environmental safety, thus possessing significant industrialization prospects.
[0085] All performance parameters involved in the embodiments and comparative examples of this invention were measured using current national / international standards and industry-standard instruments in the field. Green blank forming rate and thickness shrinkage rate: 2D machine vision + AI are used to detect surface defects (scratches, bubbles, black spots, etc.) of green blanks and calculate the ratio of qualified green blanks to total green blanks.
[0086] Bending strength (MPa): Refer to the national standard GB / T6569-2006 "Test Method for Bending Strength of Fine Ceramics" (three-point bending method), span 30mm, loading rate 0.5mm / min, the testing instrument is a microcomputer-controlled electronic universal testing machine (model: Instron 5966).
[0087] Thermal conductivity (W / (m·K)): Measured at 25℃ using a laser thermal conductivity meter (model: NETZSCHLFA467) in accordance with the national standard GB / T22588-2008 "Measurement of thermal diffusivity or thermal conductivity by flash method".
[0088] Dielectric constant (1MHz): The dielectric constant and dielectric loss tangent of the structural ceramic materials for electronic components were tested using an LCR meter (model: Keysight E4980A) at a frequency of 1MHz, in accordance with the national standard GB / T5594.4-2015 "Test Methods for Performance of Ceramic Materials for Electronic Components".
[0089] Relative density: Using water as a medium, the density of a sample is measured using an automated electronic densitometer based on Archimedes' principle. The relative density is obtained by comparing the obtained density with the theoretical density.
[0090] Residual carbon content and decomposition temperature: Thermogravimetric analysis (TGA) was used. The sample was placed in a thermogravimetric analyzer, and the purging atmosphere was set to nitrogen. A heating program was set, increasing the temperature from 40℃ to 1700℃, and the mass-temperature curve (TG curve) of the sample was recorded. The mass percentage at the final plateau of the curve is the residual carbon content under those conditions. Simultaneously, the decomposition temperature was determined based on the mass loss.
[0091] The chemical reagents and ceramic raw materials used in the examples in this instruction manual are all standardized commodities commonly used in industry and laboratories. To eliminate any ambiguity in the instruction manual, the specific raw material grades, performance parameters, and acquisition methods are supplemented as shown in the table below: The above description is merely a preferred embodiment of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention. Structures, devices, and operating methods not specifically described or explained in this invention are implemented according to conventional methods in the art unless otherwise specified or limited.
Claims
1. A method for preparing alumina ceramic substrates using water-based casting molding, characterized in that, Includes the following steps, S1. Based on 100 parts by weight of micron-sized ceramic powder, the micron-sized ceramic powder, 60-70 parts by weight of deionized water, and 3-6 parts by weight of dispersant are ball-milled and mixed to prepare the first slurry. S2. Add 15-25 parts by weight of binder, 5-10 parts by weight of thickener, and 5-8 parts by weight of plasticizer to the first slurry and ball mill to prepare the second slurry. S3. Add 1 to 2 parts of defoamer to the second slurry and mix evenly to prepare the third slurry; S4. The third slurry is placed in a vacuum degassing machine for vacuum degassing; S5. Place the degassed casting slurry into the casting machine for casting to obtain a green ceramic tape. After drying, cut it to obtain green ceramic pieces. S6. The green ceramic pieces are stacked and warm-pressed to form a blank, and the pressed blank is placed in a debinding furnace for debinding. S7. Place the debonded blank into a sintering furnace for calcination, and then cool it with the furnace to obtain a ceramic substrate.
2. The method for preparing alumina ceramic substrates by water-based casting according to claim 1, characterized in that, In step S1, the particle size of the micron-sized ceramic powder is 1-3 μm; based on 100 parts by weight of the total mass of the micron-sized ceramic powder, it consists of 90-95 parts by weight of micron-sized alumina powder and 5-10 parts by weight of sintering aid; the sintering aid is one or more of magnesium calcium silicate glass, yttrium oxide, dysprosium oxide, and lithium carbonate.
3. The method for preparing alumina ceramic substrates by water-based casting according to claim 1, characterized in that, In step S1, the dispersant is one or more of ammonium citrate, polyacrylic acid, and tetramethylammonium hydroxide.
4. The method for preparing alumina ceramic substrates by water-based casting according to claim 1, characterized in that, In step S2, the adhesive is a mixture of polyvinyl alcohol and styrene-butadiene rubber; the thickener is one or both of hydrogen carboxymethyl cellulose and lithium carboxymethyl cellulose; and the plasticizer is one or more of glycerol, polyethylene glycol, and dibutyl phthalate.
5. The method for preparing alumina ceramic substrates by water-based casting according to claim 4, characterized in that, Based on 100 parts by weight of micron-sized ceramic powder, the content of polyvinyl alcohol is 5-10 parts by weight, the content of styrene-butadiene rubber is 10-15 parts by weight, and the content of thickener is 5-10 parts by weight.
6. The method for preparing alumina ceramic substrates by water-based casting according to claim 1, characterized in that, In step S3, the defoamer is one or more of tributyl phosphate and silicone oil.
7. The method for preparing alumina ceramic substrates by water-based casting according to claim 1, characterized in that, In step S4, the vacuum degassing pressure is 0.1–0.3 MPa and the time is 0.2–0.5 h.
8. The method for preparing alumina ceramic substrates by water-based casting according to claim 1, characterized in that, In step S5, the height of the squeegee during casting is 1 mm, the casting substrate is a silicone resin coated PET film, and the specific drying process is as follows: first, pre-dry in the range of 35 to 40 ℃ for 10 min, and finally dry in the range of 50 to 70 ℃ for 10 min.
9. The method for preparing alumina ceramic substrates by water-based casting according to claim 1, characterized in that, In step S6, the temperature of the warm pressing is 45-120 ℃, the pressure is 10-50 MPa, and the holding time is 1-2 h; the temperature of the glue discharge is 200 ℃-600 ℃, and the holding time is 2-3 h.
10. The method for preparing alumina ceramic substrates by water-based casting according to claim 1, characterized in that, In step S7, the specific calcination process is as follows: the temperature is raised to 1500℃~1600℃ at a heating rate of 5℃ / min in an air atmosphere, and held for 2~4 h.
Citation Information
Patent Citations
Method for preparing silicon nitride ceramic substrate by tape casting
CN119751083A
